Self-Defense of Luh Sekar in Oka Rusmini's Novel Tarian Bumi in Sigmun Freud's Concept of Psychoanalysis - Elvina Anjarini (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2023)
This study aims to analyze the self-defense mechanism carried out by a character named Luh Sekar in a novel by Oka Rusmini entitled Tarian Bumi and studied in the concept of Sigmund Freud's psychoanalytic theory. The method used in this study is descriptive qualitative method with novels as data sources and data collection tools. The focus of this research is to focus on describing the psychological condition of the main character in the contents of the novel. Data analysis here uses a description of the data in the research process that has been carried out. In this study, a result was also obtained, namely the attitude or mechanism used by the character in solving the problems he had faced. The self-defense mechanisms carried out by the characters include regression, repression, diversion and formation reactions. This is done by the character aims to find a solution to the problem of the character to solve all the problems experienced. The conclusion of this study is that the self-defense mechanism of Sigmund Freud's psychoanalytic theory explains the self-defense carried out by the character Luh Sekar in maintaining his self-image from all the many problems that exist.